KORELASI WAKTU REAKSI DAN AKSELERASI TERHADAP PRESTASI LARI 100 METER MAHASISWA PUTRA SEMESTER II PROGRAM STUDI PENJASKESREK FKIP UNIVERSITAS RIAU - Yuherdi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
Problems in this research originated from field observations indicating that students’ performance in the 100-meter sprint was relatively low, which was presumed to be influenced by acceleration ability and reaction time. This study aimed to determine the relationship between reaction time and acceleration with 100-meter running achievement of male students in the second semester of Penjaskesrek FKIP Universitas Riau. The research employed a correlational design. The population consisted of 76 male students, and using purposive sampling, 35 students were selected as the sample. Data were collected using the Whole Body Reaction Test, a 30-meter sprint test, and a 100-meter sprint test. The data were analyzed using simple and multiple product moment correlation techniques. The results showed a significant relationship between reaction time and 100-meter running performance, indicated by r_count = 0.465 > r_table = 0.334. There was also a significant relationship between acceleration and 100-meter running performance, with r_count = 0.434 > r_table = 0.334. Furthermore, a significant simultaneous relationship was found between reaction time and acceleration with 100-meter running achievement, as indicated by R_count = 0.562 > R_table = 0.334.